Avaliação do programa saúde da família no Rio Grande do Norte - Santos, Paula Fernanda Brandão Batista dos (2013)
The Family Health Program implemented in Brazilian municipalities from 1994 represents today the most promising proposal to promote important changes in municipality`s health systems, to allow universal access to health care, comprehensiveness, equity and to promote social control, achievements provided by the health reform process and incorporated to the Unified Health System principles. However, many are the challenges imposed to the Family Health Program so that it can cause these advances. In this study, we aimed to answer the following research question: what are the results of the Family Health Program in relation to beneficiaries at small, medium and large municipalities? The hypothesis that guided this work was that the variation in levels of achievement/results (strict, impacts and effects) of the Family Health Program is related to the size of the municipalities. Therefore, our general aim was to evaluate the results of the Family Health Program in municipalities at Rio Grande do Norte, Brazil. And as specific objectives, to measure strict results, effects and impacts of the Program, from the criteria of efficiency and effectiveness on the beneficiated population, and to measure the Program`s impact on the organization of municipality`s health system. This is an impact assessment research, developed from multiple case studies with quanti-qualitative approach. The study included small municipalities (Acari and Taipu), midsize (Canguaretama and Santa Cruz) and large (Natal and Mossoró). The individuals chosen to the research were users/beneficiaries of the Program and health professionals. Data analysis was performed using descriptive statistics and content analysis compared from the Program`s logical /theoretical model. The results obtained in relation to the principles evaluated (universality, comprehensiveness and community participation) presented that municipalities show different results, although not directly related to the size, but related with characteristics of the Program`s implementation form in each municipality and the arrangements made for its operationalization. The positive effect that generated significant change in people`s lives has been linked to the increase of access and to the decrease of geographic barriers. However, to the municipal health system, regarding the changes desired by the Program, it was not observed a positive impact, but a negative impact related to the increase of barriers for the user to access other levels of the health system